(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In the given article described principle of design of electromagnetic transducers of values and phases of primary current of power net to secondary voltage on the bases of new construction of magnetic transformers circuits. Classical electromagnetic current transducers – transformers (EMСT), which using in electrical nets of power supply systems, constructed on the bases a closely magnetic conversion systems - circuits, have a low accuracy during conversion, operational limitation, when the are installed in one, three and multi - phases electric nets. In the given materials analyzed of the constructions of magnetic part of electromagnetic transducers of primary current to secondary voltage which used in electrical nets of power supply systems, methods of improving their principles of design and developing of characteristics.